Hubungan Lama Menjalani Hemodialisa (HD) dengan Harga Diri Pada Pasien Gagal Ginjal Kronik di Rumah Sakit Bintang Amin Bandar Lampung - Destiana Rosa; Prima Dian Furqoni; Aryanti Wardiyah (Universitas Malahayati Lampung, 2025)
ABSTRACT Data from the International Society of Nephology in 2022 covered 6,908,440 patients, and reported a global prevalence of 13.4% for CKD stages 1–5 and 10.6% for CKD stages 3–5.8. Indonesian Health Survey (2023) The prevalence of chronic kidney failure was 638,178 cases and Lampung province 21,021 cases. Bintang Amin Hospital cases of kidney failure itself were 479 cases in 2021, 482 cases in 2022, 590 cases in 2023. To determine the relationship between the length of hemodialysis (HD) and self-esteem in chronic kidney failure patients at Bintang Amin Hospital Bandar Lampung in 2024. This type of quantitative research with a cross-sectional research design, the population is all kidney failure patients undergoing hemodialysis at the Hospital. Bintang Amin January-December 2023 as many as 190 patients, the sampling technique used was purposive sampling with a sample of 129 respondents. The instrument used a questionnaire and the statistical test used the Pearson chi square test. The frequency distribution of the average duration of hemodialysis (HD) showed that most patients had a duration of hemodialysis 24 months, (45.7%). Self-esteem showed that most patients (51.9%) had low self-esteem from 129 respondents. The results of the Pearson chi square p-value test were 0.000 ≤ 0.05. There is a relationship between the duration of hemodialysis and self-esteem in kidney failure patients at the Bintang Amin Hospital, Bandar Lampung in 2024 Keywords: Patients, Chronic Kidney Failure, Self-Esteem ABSTRAK Data dari International Society of Nephology tahun 2022 mencakup 6.908.440 pasien, dan melaporkan prevalensi global sebesar 13,4% untuk CKD stadium 1–5 dan 10,6% untuk CKD stadium 3–5.8. Survei Kesehatan Indonesia (2023) Prevalensi gagal ginjal kronik adalah 638.178 kasus dan sedangkan provinsi Lampung 21.021 kasus. Rumah Sakit Bintang Amin kasus gagal ginjal sendiri yaitu 479 kasus ditahun 2021, 482 kasus ditahun 2022, 590 kasus di tahun 2023. Diketahui hubungan lama menjalani hemodialisa (HD) dengan harga diri pada pasien gagal ginjal kronik di rumah sakit Bintang Amin Bandar Lampung tahun 2024. Jenis penelitian kuantitatif dengan rancangan penelitian cross sectional, populasi adalah seluruh pasien gagal ginjal yang menjalani hemodialisa di RS. Bintang Amin Januari-Desember 2023 sebanyak 190 pasien, teknik sampling yang digunakan adalah purposive sampling dengan sampel 129 responden. Instrumen menggunakan kuesioner dan uji statistic yang digunakan uji pearson chi square. Distribusi frekuensi rata-rata lama hemodialisa (HD) didapatkan bahwa sebagian besar pasien lama hemodialisa 24 bulan, (45,7%). Harga diri didapatkan bahwa sebagian besar pasien (51,9%) harga diri rendah dari 129 responden. Hasil uji pearson chi square pvalue 0,000 ≤ 0,05. Ada hubungan lama menjalani hemodialisa dengan harga diri pada pasien gagal ginjal di Rumah Sakit Bintang Amin Bandar Lampung tahun 2024 Kata Kunci: Pasien, Gagal Ginjal Kronik, Harga Diri